High prevalence of infection and low incidence of disease in child contacts of patients with drug-resistant tuberculosis: a prospective cohort study. Issue 7 (6th December 2018) - Huerga, Helena; Sanchez-Padilla, Elisabeth; Melikyan, Nara; Atshemyan, Hakob; Hayrapetyan, Armen; Ulumyan, Ani; Bastard, Mathieu; Khachatryan, Naira; Hewison, Catherine; Varaine, Francis; Bonnet, Maryline
Abstract : Objective: We aimed to measure the prevalence and incidence of latent tuberculosis infection (LTBI) and tuberculosis (TB) disease in children in close contact with patients with drug-resistant TB (DR-TB) in a country with high DR-TB prevalence. Design and setting: This is a prospective cohort study of paediatric contacts of adult patients with pulmonary DR-TB in Armenia. Children were screened using tuberculin skin test, interferon-gamma release assay and chest X-ray at the initial consultation, and were reassessed every 3–6 months for a period of 24 months. Children did not receive preventive treatment. Main outcome measures: Prevalence and incidence of LTBI and TB disease; factors associated with prevalent LTBI. Results: At initial evaluation, 3 of the 150 children included were diagnosed with TB disease (2.0%). The prevalence of LTBI was 58.7%. The incidence of LTBI was 19.9 per 100 children per year, and was especially high during the first 6 months of follow-up (33.3 per 100 children per year). No additional cases with incident disease were diagnosed during follow-up. After adjustment, prevalent LTBI was significantly associated with the child's age, sleeping in the same house, higher household density, the index case's age, positive smear result and presence of lung cavities. Conclusions: Children in close contact with patients with DR-TB or in contact with very contagious patients had an increased risk of prevalent LTBI. Although none of the children developed TB disease during a 2-year follow-up period, screening for symptoms of TB disease, based on the prevalence of disease at recruitment, together with follow-up and repeated testing of non-infected contacts, is highly recommended in paediatric contacts of patients with DR-TB.